2017
DOI: 10.1007/s10143-017-0927-8
|View full text |Cite
|
Sign up to set email alerts
|

Oblique retroperitoneal approach for lumbar interbody fusion from L1 to S1 in adult spinal deformity

Abstract: In recent years, with advancements in surgical techniques and instrumentation, the lateral lumbar interbody fusion is being used increasingly as an alternative procedure to anterior approach. In this study, we illustrated a oblique retroperitoneal approach for lumbar interbody fusion with one incision site and tilting of the operation table in adult spinal deformity and evaluate the radiographical findings and clinical outcomes of patients treated using this technique. This study included 32 patients scheduled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 42 publications
1
57
0
Order By: Relevance
“…Recently, a few of clinical studies have demonstrated the technical advantages and favorable outcomes of OLIF therapy for lumbar degenerative diseases, mainly involving the L2-5 segments [2,[5][6][7]. Bearing these bene ts in mind, there has been cautious endeavor for the usage of OLIF at the lumbosacral junction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a few of clinical studies have demonstrated the technical advantages and favorable outcomes of OLIF therapy for lumbar degenerative diseases, mainly involving the L2-5 segments [2,[5][6][7]. Bearing these bene ts in mind, there has been cautious endeavor for the usage of OLIF at the lumbosacral junction.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative technique to lateral lumbar interbody fusion (LLIF), the OLIF procedure has several theoretical advantages over LLIF, such as avoiding psoas muscle disruption and lumbosacral plexus injury, consistent access to the lower lumbar levels without the need for neuromonitoring [3,4]. Recently, OLIF has been generally recognized as an effective procedure in the treatment of various spinal pathologies at L2-L5 segments, including degenerative disc disease, lumbar spondylosis, spondylolisthesis, lumbar stenosis and scoliosis [2,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the scoliosis research society–Schwab classification of adult scoliosis proposed by Schwab, the three revised parameters of the sagittal vertical axis (SVA, cm), pelvic tilt (PT, °), and pelvic incidence‐lumbar lordosis (PI‐LL, °) are considered to be closely related to the quality of life. Some scholars believe that SVA <50 mm, PT <20°, and LL‐PI <10°are attributed to the thresholds of health. They can be used as important references for the surgeon to evaluate the sagittal balance of ADS patients before surgery and to formulate the operation plan.…”
Section: Development Of Oblique Lumbar Interbody Fusionmentioning
confidence: 99%
“…Postoperative pain scores improved. Kim et al . performed OLIF on 32 patients with scoliosis deformity.…”
Section: Development Of Oblique Lumbar Interbody Fusionmentioning
confidence: 99%